1956
DOI: 10.1099/00221287-14-3-634
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation Behaviour and Electron Microscopic Examination of Purified Influenza Virus

Abstract: . Melt)ourne, AustraliaPurified preparations of influenza virus were examined in the ultracentrifuge and electron microscope principally to assess the degree of purification achieved. As indicated in the main paper (Ada & Perry, 1956) the same purification procedure was used foir each batch of virus. METHODS Ultracentrifugation.The virus was examined in 0.85 yo NaCl solution (w/v) a t a concentration varying between 0.2 and 0.4 yo (w/v). The ultracentrifuge was air-driven of the Beams-Pickels type. The speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1957
1957
1968
1968

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Well studied strains such as PR8 and LEE were found to consist mainly of irregularly round objects, approximately 75 mji, in diameter (Williams and Wyckoff, 1945), Occasionally elongated forms appeared which were quite distinct in size and appearance (Mosley and Wyckoff, 1946;Heiraoats, 1948). These observations were confirmed by Chu, Dawson and Elford (1949), who found that these filaments were extremely rare in old laboratory strains such as PR8 and LEE, The physical nature of ' 'incomplete virus" (von Magnus, 1947(von Magnus, , 1951b has also been intensively investigated, Gard and von Magnus (1947) and Gard et al, (1952) Schlesinger, 1954;Toss and Wengel, 1955;Pye et al, 1956;Hollos, 1957) Once the identity of the virus particle was established Williams (1950). No attempt was made in either of theee studies to relate particle counts to biological activity.…”
mentioning
confidence: 78%
“…Well studied strains such as PR8 and LEE were found to consist mainly of irregularly round objects, approximately 75 mji, in diameter (Williams and Wyckoff, 1945), Occasionally elongated forms appeared which were quite distinct in size and appearance (Mosley and Wyckoff, 1946;Heiraoats, 1948). These observations were confirmed by Chu, Dawson and Elford (1949), who found that these filaments were extremely rare in old laboratory strains such as PR8 and LEE, The physical nature of ' 'incomplete virus" (von Magnus, 1947(von Magnus, , 1951b has also been intensively investigated, Gard and von Magnus (1947) and Gard et al, (1952) Schlesinger, 1954;Toss and Wengel, 1955;Pye et al, 1956;Hollos, 1957) Once the identity of the virus particle was established Williams (1950). No attempt was made in either of theee studies to relate particle counts to biological activity.…”
mentioning
confidence: 78%
“…It is of interest in this regard that morphologic evidence supporting the similarity between the cytoplasmic fragments and incomplete virus is provided by electron microscopic examination of purified preparations. Dried-down suspensions of incomplete virus contain particles which are pleomorphic, generally larger than infectious virus and flattened in appearance, often resembling empty sacs (18,(23)(24)(25)(26)(27). Moreover, many of the forms observed in sectioned pellets (28) closely resemble the particles illustrated in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…1 and noted in a previous publication, reference 8). Filaments, however, do not appear to constitute the incomplete forms associated with undiluted inocula for they were not especially numerous in the thin sections examined, nor do they appear to make up a significant proportion of the particles seen in purified preparations (18,(23)(24)(25)(26)(27)(28).…”
Section: Studies Of Incomplete Iintlitenza Virusmentioning
confidence: 95%